Multivariate analysis of ginger (Zingiber officinale Rosc.) germplasm of North Eastern India - Kumar, A; Kapoor, C; Rahman, H; Karuppaiyan, R; Rai, S; Denzogpa, R (The Indian Journal of Genetics and Plant Breeding, 2016)
Eighty two ginger (Zigiber officinale Roc.) accessions collected from North-Eastern region of India were subjected to study genetic diversity considering 12 quantitative and 7 qualitative characters using multivariate analysis. Considerable variation was recorded among ginger accessions for all the morphological traits studied. Yield showed significant but not of high degree correlation with eight characters studied. Most of the qualitative characters were found to be non-significantly correlated among themselves and with quantitative characters. Principal component analysis based on different characteristics grouped the germplasm into eight clusters. Seven cultivars found to yield consistently well under organic conditions. Considerable variation was observed among the clones related to internal colour of rhizome and pungency.